Renewable Energy in Europe: Strong Political Will Required for Ambitious Goals - Jochen Diekmann (Weekly Report, 2009)
A number of substantive goals and mechanisms for implementing an integrated climate and energy policy have been ratified over the last two years at the European level. By 2020, greenhouse gas emissions in Europe are to be reduced by at least 20 percent; energy efficiency improved by 20 percent; and the share of energy from renewable sources increased to 20 percent. According to a recent European Council decision, by 2050 greenhouse gas emissions in Europe are to be reduced by as much as 80 to 95 percent. In June of 2009 a new EU Directive was enacted for the promotion of renewable energy. The Directive sets binding goals for the share of energy from renewable sources in the 27 Member States by 2020 while also defining conditions for their achievement. The Directive replaced existing EU directives that had only set non-binding targets for electricity and fuels from renewable energy for 2010. These Directives have only been of limited effectiveness. Individual EU Member States must now immediately address how they plan to meet these requirements by devising and implementing appropriate domestic policy measures. Germany is in a good starting position for the further expansion of renewables, particularly because of its overhauled Renewable Energy Sources Act (EEG) and the new Renewable Energy Heat Act (EEWärmeG). Nevertheless, the new German government faces great challenges in integrating larger amounts of renewable energy into the energy economy at an accelerated pace.
Keywords: Q2; Q4; Q5; 330; Renewable Energy; Promotion Policy; European Union